Introduction to Weak Measurements and Weak Values - Boaz Tamir; Eliahu Cohen (Quanta)
We present a short review of the theory of weak measurement. This should serve as a map for the theory and an easy way to get familiar with the main results, problems and paradoxes raised by the theory.